Frequency, diversity, and productivity study on the Aedes aegypti most preferred containers in the City of Manaus, Amazonas, Brazil - Pinheiro, Valéria Cristina Soares; Tadei, Wanderli Pedro (Revista do Instituto de Medicina Tropical de Sao Paulo, 2002)
The most preferred containers by Aedes aegypti were studied April and July (rainy and dry periods) in two Manaus neighbourhoods. In all, 2,700 premises and 13,912 containers were examined, most (87%) recorded outdoors. Out of the 13,100 inspected premises, only 1.6% showed to be positive for Aedes aegypti, summing up to 7,916 collected samples. Most frequently found containers outdoors in either neighbourhood regardless of rain or dry period were Bottles flasks and Storage, and indoors, Fixed, Flowerpots, and buckets. Productivity was estimated according to the number of premises and positive containers investigated, showing the actual container groups productivity. Considering both rainy and dry periods outdoors at Praça 14 the groups of Tyre, Flask, Bottle, Construction Equipment and Fixed, had the highest averages respectively. Construction Equipment and Flask groups were the most productive in Coroado in April. Flask, Construction Equipment and Storage groups stood out in July.
Keywords: Rain; Aedes; Animals; Dengue; Disease Carrier; Growth, Development And Aging; Insect; Mosquito; Population Density; Season; Aedes; Animal; Dengue; Disease Reservoirs; Insect Vectors; Mosquito Control; Population Density; Pupa; Rain; Seasons